Leiomyosarcoma and Squamous Cell Carcinoma Arising in Mature Cystic Teratoma of the Ovary - Tip Pongsuvareeyakul; Kornkanok Sukpan; Somjet Chaicharoen; Surapan Khunamornpong (Case Reports in Pathology)
The occurrence of malignant transformation in mature cystic teratoma of the ovary is rare, with squamous cell carcinoma being the most common histologic type. Sarcomatous transformation has been rarely described in the literature. We present a case of leiomyosarcoma with a minor component of squamous cell carcinoma arising in mature cystic teratoma of ovary in a 65-year-old woman. The malignant tumor showed two distinct components of sarcomatous and invasive epithelial elements, which were confirmed by immunostaining. To our knowledge, only four cases of leiomyosarcoma in ovarian mature cystic teratoma have been reported and this is a unique case report of leiomyosarcoma and squamous cell carcinoma arising in a mature cystic teratoma of ovary.